Metal ion type significantly affects the morphology but not the activity of lipase–metal–phosphate nanoflowers. Issue 41 (11th May 2017) - Sharma, N.; Parhizkar, M.; Cong, W.; Mateti, Srikanth; Kirkland, M. A.; Puri, M.; Sutti, A.
Abstract : Using different metal ions to prepare hybrid lipase nanoflowers resulted in a variety of different morphologies, but did not significantly affect the specific activity of the enzyme. Abstract : Enzyme–metal-ion–phosphate nanoflowers are high-surface area materials which are known to show higher activity than the constituting protein. Although the synthesis of hybrid nanoflowers has been demonstrated with a variety of proteins and reaction conditions, only di-valent metal ions have been tested to date. We expand on previous findings by testing a range of metal ions of different valence in co-presence with lipase from Burkholderia cepacia : Ag(i ), Fe(ii ), Cu(ii ), Au(iii ). All metal ions produced colour precipitates, although the type of metal caused different precipitate morphologies under comparable reaction conditions: from nanoflowers to forests of nano-plates and crystal-like precipitates. In contrast, the type of metal ion did not appear to significantly affect the product's specific enzyme activity, which remained greater than that of free lipase. This indicates that the type of metal ion and the macroscopic arrangement of the petals play a secondary role to that of the co-presence of the metal and phosphate ions in determining lipase nanoflower activity. The demonstrated ability to produce metal–phosphate-protein nanoflowers with a selection of different metals also opens the way to producing a wider range of functional, nanostructured, materials.